2019
DOI: 10.3389/fonc.2019.00246
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Heterogeneity Can Be Explained Beyond the Genome

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains a major health problem because it induces almost systematic mortality. Carcinogenesis begins with genetic aberrations which trigger epigenetic modifications. While genetic mutations initiate tumorigenesis, they are unable to explain the vast heterogeneity observed among PDAC patients. Instead, epigenetic changes drive transcriptomic alterations that can regulate the malignant phenotype. The contribution of factors from the environment and tumor microenvironment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 67 publications
0
62
0
Order By: Relevance
“…The application of this algorithm to histopathologically unclassifiable tumors identifies two patient groups with significantly different overall survival. We therefore hypothesize that the algorithm is capable of re-identifying the dominant features of the QM and non-QM molecular subtypes in CT images and that radiomics-based phenotyping may thus offer a clinically usable classification advantageous over histopathology in the notoriously heterogenous entity of PDAC [18][19][20]. This notion is reinforced by the fact that histopathological samples are by default a significant underrepresentation of the tumor, since they are derived from a small sub-section of the tissue [21], and regions of differing molecular subtype are likely to coexist within the same tumor [22].…”
Section: Discussionmentioning
confidence: 99%
“…The application of this algorithm to histopathologically unclassifiable tumors identifies two patient groups with significantly different overall survival. We therefore hypothesize that the algorithm is capable of re-identifying the dominant features of the QM and non-QM molecular subtypes in CT images and that radiomics-based phenotyping may thus offer a clinically usable classification advantageous over histopathology in the notoriously heterogenous entity of PDAC [18][19][20]. This notion is reinforced by the fact that histopathological samples are by default a significant underrepresentation of the tumor, since they are derived from a small sub-section of the tissue [21], and regions of differing molecular subtype are likely to coexist within the same tumor [22].…”
Section: Discussionmentioning
confidence: 99%
“…PDAC has one of the worst prognoses of any common solid tumors with a 5-year survival rate of around 5-8% [1,4]. The adverse prognosis in most cases is due to diagnosis at advanced disease stages and only up to 20% of patients are candidates for surgical resection in curative intent [5,6]. Most PDACs are associated with somatic mutations, most frequently in the KRAS, TP53, CDKN2A, and SMAD4 genes.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that primary and metastatic PDACs had significantly lower expression of KMT2D and loss of KMT2D promoted PDAC invasion and migration, which supports a tumor-suppressive role of KMT2D in PDAC. Loss of KMT2D also induced a gene signature closely resembling the Moffitt basal-like subtype, which confers a significantly worse prognosis compared to the classical subtype 21,45,46 . These PDAC subtypes have distinct epigenetic landscapes that drive transcriptional alterations.…”
Section: Discussionmentioning
confidence: 98%